2020
DOI: 10.24187/ecostat.2020.514t.2010
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Social Exclusion and Resources of Young NEETs

Abstract: The opinions and analyses in this article are those of the author(s) and do not necessarily reflect their institution's or Insee's views. ReferencesÉconomie et Statistique N° 283-284, 1995. Les trajectoires des jeunes : transitions professionnelles et familiales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 158 publications
(213 reference statements)
1
7
0
2
Order By: Relevance
“…Sergi, Cefalo, and Kazepov (2018) share the opinion that institutionalising NEETyouth as an analytical category may prove problematic since it may not clearly identify specific vulnerable subcategories, thereby leading to ineffective one-sizefits-all policy interventions. Therefore, if policy and communication is based solely on the term NEET-youth, then the available evidence suggests the need for a broader categorisation of NEET-status, as policy interventions may not meet the needs of many young people (Maguire 2018;Bonnard, Giret and Kossi 2020). When creating services for the youth and communicating about them, it must be considered that young people are NEETs for different reasons, and mostly temporarily (Suttill 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sergi, Cefalo, and Kazepov (2018) share the opinion that institutionalising NEETyouth as an analytical category may prove problematic since it may not clearly identify specific vulnerable subcategories, thereby leading to ineffective one-sizefits-all policy interventions. Therefore, if policy and communication is based solely on the term NEET-youth, then the available evidence suggests the need for a broader categorisation of NEET-status, as policy interventions may not meet the needs of many young people (Maguire 2018;Bonnard, Giret and Kossi 2020). When creating services for the youth and communicating about them, it must be considered that young people are NEETs for different reasons, and mostly temporarily (Suttill 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the political term for the target group (NEET) may lead to stigmatisation of young people which, in turn, affects access to the services and therefore accepting (necessary) help (Maguire 2018;Holte 2018;Bonnard, Giret and Kossi 2020). This may create a situation where services actually have a stigmatising effect whereby the youth feel that they are being labelled, or that their lives are overly directed without them being able to contribute to their own goals.…”
Section: Reasons and Solutions For Neet Statusmentioning
confidence: 99%
“…Based on the analysis of the literature overview, it may be concluded that research related to the concept NEET is mainly divided into three categories: research papers that show that the concept used for NEETs (NEET, not in Education, Employment, or Training) is too general and does not allow to see the heterogeneity of the target group (1), research that identifies the limiting and enabling factors based on the concept referring to the target group (2) and research that provides guidance on the use and interpretation of national data related to the target group (3) (Figure 3). Sergi et al (2018) suggest that institutionalizing NEET-youth as an analytical category may prove problematic since it may not clearly identify specific vulnerable subcategories, leading to ineffective one-size-fits-all policy interventions (Cabasés Piqué et al, 2016) and as broad policy interventions may not meet the needs of many young people (Maguire, 2018;Bonnard et al, 2020). Understanding the lifestyle of young people from their perspective is essential for policy-making (Poštrak et al, 2020).…”
Section: "Neet" As a Conceptmentioning
confidence: 99%
“…For young people, other factors may play a role. Belonging to a disadvantaged social background, lacking educational qualifications or training (Bonnard et al, 2020), and becoming NEET (Not in Employment, Education, or Training) are factors that contribute to vulnerability and present challenges in career progression (Bojadjieva et al, 2022). Other psychosocial factors such as family problems, social isolation, loneliness, and social and academic inactivity (Berthet & Longo, 2021) are also considered risk situations.…”
Section: Assisting Vulnerable Individuals In Confronting the Crises O...mentioning
confidence: 99%